ANALISIS WAKTU KERJA LEMBUR DAN UPAH KERJA LEMBUR BERDASARKAN UNDANG-UNDANG CIPTA KERJA NO. 6 TAHUN 2023 (STUDI KASUS CV CAKRA UTAMA DEPOK) - Adelya, (2024)
This study aims to find out how the provisions regarding overtime work time and overtime work wages at CV Cakra Utama Depok and legal sanctions are regulated. This research uses normative juridical research methods conducted by interviewing the owner and workers at CV Cakra Utama. Based on the results of the research, it can be concluded that the implementation of overtime and overtime wages at CV Cakra Utama has not been fully implemented in accordance with Government Regulation No. 35 of 2021. Researchers also found that the minimum wage given by CV Cakra Utama is not in accordance with the provisions of the West Java provincial minimum wage, especially in the Depok City area where welding workshops are included in the SME (Small and Medium Enterprises) category. Therefore, it can be concluded that CV Cakra Utama committed a criminal offense that does not result in imprisonment but only fines and confinement.